PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KUALITAS PELAPORAN KEUANGAN DAN DAMPAKNYA PADA EFISIENSI INVESTASI: Penelitian pada Perusahaan Manufaktur yang terdaftar pada Bursa Efek Indonesia - Teguh Budi Raharjo (JURNAL STIE SEMARANG, 2020)
This study analyzes and describes the condition of the financial reporting quality manufacturing company in Indonesia, determinants and impact. The deciding factor analyzed the quality of financial reporting is characteristic of companies that include the structure of the company (firm structure), monitoring the company (firm monitoring) and firm performance. The goal of this research is to analyze and generate empirical findings about the effect of the structure of the company, monitoring the company and the company's performance against the quality of financial reporting and the influence of the corporate structure, the monitoring company, the company's performance and the quality of financial reporting on the efficiency of investment. The benefits of this research are expected to contribute ideas for the development of science primarily related financial accounting and financial reporting quality influencing factors (characteristics of the company) and its implications on the efficiency of investment. Methods of data collection is done by documentation. While the method of nanalysis performed by Path Analysis. The study concluded that of the three variables that were analyzed, only performance and monitoring variables proved to affect the quality of financial reporting. The variable structure of the companies does not affect the quality of financial reporting. Associated with the efficiency of investment, generally of four independent variables were analyzed (structure, monitoring, performance, quality financial reporting) affect not directly on the efficiency of investment. Nonetheless, the indirect effect, and the proven performance monitoring variables affecting the efficiency of investment. Both of these variables affect the efficiency of investment through the end of the financial reporting quality